Electrochemical Assessment of Mitigation of Desulfovibrio ferrophilus IS5 Corrosion against N80 Carbon Steel and 26Cr3Mo Steel Using a Green Biocide Enhanced by a Nature-Mimicking Biofilm-Dispersing Peptide - Lingjun Xu; Pruch Kijkla; Sith Kumseranee; Suchada Punpruk; Tingyue Gu (MDPI AG, 2023)
MIC (microbiologically influenced corrosion) is problematic in many industries, especially in the oil and gas industry. In this work, N80 carbon steel for pipelines was tested with 26Cr3Mo chromium pipeline steel for comparison in SRB (sulfate-reducing bacterium) MIC mitigation using a THPS (tetrakis hydroxymethyl phosphonium sulfate)-based commercial biocide (Biotreat 5475 with 75-80% THPS by mass). Peptide A, a nature-mimicking synthetic cyclic peptide (cys-ser-val-pro-tyr-asp-tyr-asn-trp-tyr-ser-asn-trp-cys) with biofilm dispersal ability was used as a biocide enhancer. Metal coupons covered with 3-d old Desulfovibrio ferrophilus IS5 biofilms were immersed in different biocide solutions. After 1-h treatment, 200 ppm Biotreat 5475, 200 ppm Biotreat 5475 + 200 nM (360 ppb) Peptide A, and 400 ppm Biotreat 5475 achieved 0.5-log, 1.7-log and 1.9-log reductions in sessile cell count on N80, and 0.7-log, 1.7-log, and 1.8-log on 26Cr3Mo, respectively. The addition of 200 nM Peptide A cut the THPS biocide dosage by nearly half. Biocide injection tests in electrochemical glass cells after 1 h exhibited 15%, 70%, and 72% corrosion inhibition efficiency (based on corrosion current density) on N80, and 27%, 79%, 75% on 26Cr3Mo, respectively. Linear polarization resistance and electrochemical impedance spectrometry results also indicated antimicrobial efficacies.